Highly efficient metal(iii) porphyrin and salen complexes for the polymerization of: Rac -lactide under ambient conditions - Siriwan Praban (2020)
© 2019 The Royal Society of Chemistry. Ligated metal(iii) complexes, Al(iii), In(iii), Cr(iii), and Co(iii), containing tetraphenylporphyrin (TPP) and cyclohexylsalen (Cy-salen) ligands were investigated for the polymerization of rac-lactide (rac-LA). A combination of metal complexes, co-catalyst, and co-initiator was shown to be highly efficient for the ring-opening polymerization of rac-LA at room temperature. Influences of metal centers, ligands, and co-catalysts were investigated. Higher Lewis acidity of metal centers and ligands enhanced catalytic activity. Ionic co-catalysts showed increased polymerization rates. Polymerization of rac-LA catalyzed by tetraphenylporphyrin aluminum chloride ((TPP)AlCl) and bis(triphenylphosphine)iminium chloride (PPN + Cl - ) in cyclohexene oxide (CHO) as a solvent produced isotactic-enriched polylactide. The order of reactivities based on the metals supported by the TPP ligand is Cr(iii) > Al(iii) > In(iii) > Co(iii) while the reactivities of the catalysts supported by Cy-salen ligands are in the order In(iii) > Cr(iii) > Al(iii) > Co(iii).